Keanekaragaman dan persebaran lalat buah Tribe Dacini (Diptera: Tephritidae) di Kabupaten Bogor dan sekitarnya - Anik Larasati; Purnama Hidayat; Damayanti Buchori (Jurnal Entomologi Indonesia, 2013)
Bogor and its surrounding area is known as one of the region in West Java that has high diversity of horticultural plants that may have an affect on fruit fly diversity. Research on fruit fly diversity is not merely provide information on the species richness of fruit flys but also provide information on its distribution and dispersion. The aim of this research was to investigate the diversity and distribution of fruit flies species and their hosts in Bogor and its surrounding area. Fruit flies were collected from 119 sampling areas in Bogor Cianjur, Bekasi and Depok. Fruit flies were sampled using two methods, i.e. host rearing and trapping. Traps were modified from Lynfield traps and combined with two different attractants, i.e. metil eugenol (ME) and Cue lure (CL). We found 18 species of fruit flies collected from traps and 24 host plants. The result showed that distribution, diversity and abundance of fruit flies was influenced by the diversity of host plants.